Kesantunan Tindak Tutur Ekspresif Memuji dalam Kolom Komentar Akun Instagram - Atika Elsa Witri; Siti Ainim Liusti (Asian Journal of Islamic Studies and Da'wah, 2026)
Linguistic politeness in online interactions is an important indicator of the quality of social relations on social media, including in Instagram comment sections, which are widely used by netizens to express appreciation and support. This study aimed to describe the politeness of expressive speech acts of praising used by netizens in Instagram comment sections. A descriptive qualitative approach was employed, with data consisting of utterances containing praise in the comment sections of three Instagram accounts, namely @jharnabhagwani, @ma.rinpo, and @arriind_. The data were collected from photo and video posts uploaded during the period July–August 2025 using observation and documentation methods, then analyzed by applying Leech’s politeness principle, which comprises six maxims: the maxim of approbation, maxim of agreement, maxim of modesty, maxim of tact, maxim of sympathy, and maxim of generosity. The findings show that, from the 130 data points analyzed, all politeness maxims were identified, with the maxim of approbation being the most dominant, indicating that Instagram comment sections function as interaction spaces oriented toward providing appreciation and positive support. In addition, the situational context of the speech event, such as the relationship between speaker and hearer, communicative goals, and the characteristics of digital communication—influenced the realization of each politeness maxim. These results demonstrate that expressive speech acts of praising on Instagram not only represent speakers’ psychological attitudes but also play a role in maintaining politeness and building harmonious social relations in digital spaces.